ANALYSIS OF FINANCIAL OF FISHERY PRODUCT PROCESSING BUSINESS IN PRODUCTION HOUSE “IBU SITI RAHMAH” IN MUARA ADANG VILLAGE PASER REGENCY - Zahrotul Widiah; Fitriyana Fitriyana; Nurul Ovia Oktawati (Jurnal Perikanan Unram, 2024)
This study aims to determine the profitability of the business and to determine the financial feasibility of fishery product processing business in the production house “Mrs. Siti Rahmah” with discounted investment criteria (NPV, IRR, and Net B/C) and non-discounted (Payback Period). This research was conducted in October 2023. The determination of respondents is guided by the sample method, with the selected respondents being fishery product processing businesses in the “Mrs. Siti Rahmah” production house. The analytical tools used in this research are cost analysis, revenue, profit, and also financial feasibility analysis with discounted and non-discounted investment criteria. The results showed that the fishery product processing business in the production house “Mrs. Siti Rahmah” in Muara Adang Village, Long Ikis Subdistrict, Paser Regency received Rp 44,880,000/year and earned a profit of Rp 9,775,782/year. From the financial aspect, the fishery product processing business is feasible to run and develop with an NPV value of Rp 50,081,700, IRR of 79%, Net B/C of 2.84 and PP of 1.19 years.